Como devo faze (a=b) (a-b), para a =2 e b= 3 ?
vamuqvamu:
confira essa equação pois ela tem um (a=b) que não faz muito sentido
Respostas
respondido por:
1
Subistituindo fica
(a+b)(a-b) => (2+3)(2-3) => (5)(-1) => -5
espero ter ajudado
(a+b)(a-b) => (2+3)(2-3) => (5)(-1) => -5
espero ter ajudado
respondido por:
1
(a+b) (a-b), para a =2 e b= 3
(2+3) (2-3)
5(-1)
- 5
(2+3) (2-3)
5(-1)
- 5
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás